Perspectives in Diagnosis and Therapeutics in Hematology - Ruiz Argüelles, Guillermo José; Gómez Almaguer, David (Instituto Nacional de la Nutrición, 2021)
In this article, the perspectives on both the diagnosis and treatment of acute leukemias, chronic leukemias, multiple myeloma, anemia, platelet, and coagulation disorders are briefly discussed. We emphasize the limitations facing the practice of hematology in low- and middle-income countries.